2019
DOI: 10.1111/jpc.14717
|View full text |Cite
|
Sign up to set email alerts
|

Effect of helmet therapy in the treatment of positional head deformity

Abstract: Aim: Most positional head deformities can be treated conservatively with postural correction training or a head orthosis ('helmet'). We aimed to investigate whether infants with helmet therapy have cosmetic improvement in head deformity. Methods: A total of 376 infants at age 2-40 months who were diagnosed with mild-moderate-severe positional head deformity were enrolled. Among these infants, 101 infants were treated with helmet therapy or postural correction training. After matching by infant's age and time o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Figure 1e presents an example of unilateral lambdoid synostosis, which accounts for 0~5% of all cases of craniosynostosis, with premature fusion of one side of the lambdoid suture flattening the back of the skull on one side and causing it to protrude on the opposite side. Analyzing the surgical effects of craniosynostosis requires a quantitative assessment of the morphological changes in the skull before and after the surgery, but it is still performed by a clinician's visual inspection of the overall head shape or by measuring the cephalic index (CI) [2,3] and cranial vault asymmetry index (CVAI) [4,5]. The CI is usually calculated as the ratio of the maximum width of the skull divided by the maximum length Analyzing the surgical effects of craniosynostosis requires a quantitative assessment of the morphological changes in the skull before and after the surgery, but it is still performed by a clinician's visual inspection of the overall head shape or by measuring the cephalic index (CI) [2,3] and cranial vault asymmetry index (CVAI) [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1e presents an example of unilateral lambdoid synostosis, which accounts for 0~5% of all cases of craniosynostosis, with premature fusion of one side of the lambdoid suture flattening the back of the skull on one side and causing it to protrude on the opposite side. Analyzing the surgical effects of craniosynostosis requires a quantitative assessment of the morphological changes in the skull before and after the surgery, but it is still performed by a clinician's visual inspection of the overall head shape or by measuring the cephalic index (CI) [2,3] and cranial vault asymmetry index (CVAI) [4,5]. The CI is usually calculated as the ratio of the maximum width of the skull divided by the maximum length Analyzing the surgical effects of craniosynostosis requires a quantitative assessment of the morphological changes in the skull before and after the surgery, but it is still performed by a clinician's visual inspection of the overall head shape or by measuring the cephalic index (CI) [2,3] and cranial vault asymmetry index (CVAI) [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Analyzing the surgical effects of craniosynostosis requires a quantitative assessment of the morphological changes in the skull before and after the surgery, but it is still performed by a clinician's visual inspection of the overall head shape or by measuring the cephalic index (CI) [2,3] and cranial vault asymmetry index (CVAI) [4,5]. The CI is usually calculated as the ratio of the maximum width of the skull divided by the maximum length Analyzing the surgical effects of craniosynostosis requires a quantitative assessment of the morphological changes in the skull before and after the surgery, but it is still performed by a clinician's visual inspection of the overall head shape or by measuring the cephalic index (CI) [2,3] and cranial vault asymmetry index (CVAI) [4,5]. The CI is usually calculated as the ratio of the maximum width of the skull divided by the maximum length from the top view of the volume as rendered by a 3D CT, and is commonly used as a severity index for sagittal and bilateral coronal cases characterized by a symmetric shape.…”
Section: Introductionmentioning
confidence: 99%
“…Plagiocephaly is a deformity where in the head of an infant can become flattened on one side, causing the head to appear asymmetrical and distorted. Brachycephaly is a deformity in which the entire back of head can become flattened, leading to widening of the head and sometimes the forward-facing part of the skull may bulge out in compensation to it [1,2]. Positional skull deformities are considered to be among the most frequently encountered difficulties during the child growth and development, especially in infants below 6 months of age.…”
Section: Introductionmentioning
confidence: 99%
“…The use of repositioning therapy in the treatment of PSD has shown to be effective in case of infants below 6 months of age, whereas helmet therapy is said to be more effective and has shown more favourable outcomes when compared to repositioning therapy. It seems to isolate out peripheral factors that intensifies the risk of repositioning therapy failure (for example: in case of infants more than 4 months of age, helmet therapy is more reliable than repositioning therapy as the infant's skull starts to harden and the head movements increases [1]. The determination of the study is to review various literature to analyse the effectiveness of helmet therapy in infants with positional skull deformity.…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, a dynamic cranial helmet improved the deformity and permitted acceptable growth of the cranium [1,25]. In this line, a systematic review on non-surgical treatment of cranial deformities showed that CHT helmet therapy may reduce skull asymmetry more effectively than postural correction training [26].…”
Section: Introductionmentioning
confidence: 99%